Killed at the whim of a hat - Cotterill, Colin (New York : Minotaur Books, 2011)
Forced to relocate to rural Thailand with her eccentric family, crime reporter Jimm Juree fears that her career is over until the bodies of two hippies are discovered in a local farmer's field and a Buddhist abbot is murdered, a case that implicates a monk and a nun.
"First published in Great Britain by Quercus"--T.p. verso.
Keywords: Women journalists -- Thailand -- Fiction; Hippies -- Crimes against -- Thailand; Buddhist monks -- Crimes against -- Thailand; Reporters and reporting -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction